psychological emotions, storytelling, artistic expression, primary-school pupils (Journal of the College of Basic Education, 2023)
The research aimed to identify the psychological emotions of the storytelling in the artistic expression of primary-school pupils' drawings. The researcher constructed analytical form consisting of 10 items to measure the psychological emotions of the storytelling . The form was validated by a jury of experts . Moreover , it was distributed to eight-pupil pilot sample to check its reliability. The final version of the form was distributed to a sample of 64 pupils chosen intentionally. SPSS software package was used to process the collected data. The findings revealed the positive impact of the storytelling in the artistic expression of primary-school pupils' drawings. The researcher recommended the use of storytelling in delivering information to pupils of other realms of art which depend in its structure on expanding intellectual side to embody the required skill. It was also recommended to involve experts and highly qualified staff in utilizing and adopting storytelling as a method to achieve understanding and learning.